KALICEPHALUS SUBULATUS MOLIN, 1861 (NEMATODA, DIAPHANOCEPHALIDAE) IN BOA CONSTRICTOR LINNAEUS, 1758 (REPTILIA, BOIDAE) OF PERU - Gómez, Luis (2007)
We report the presence of nematode, Kalicephalus subulatus Molin, 1861, that was collected in twospecimens Boa constrictor Linnaeus, 1758 from localities of Nayta, Iquitos, Loreto (3º45´30,73´´ S,73º15´04,71´´W) and LLuyllucucha, Moyabamba, San Martín (6º02´02,57´´ S, 76º58´16,95´´W). Onehundred and two nematods (52 females and 50 males) were studied and identified as K. subulatus. Thediscovery of this species in B. constrictor is the first record in Peru.